A phase I safety and immunogenicity dose escalation trial of plague vaccine, Flagellin/F1/V, in healthy adult volunteers (DMID 08-0066). Issue 48 (4th December 2017) - Frey, Sharon E.; Lottenbach, Kathleen; Graham, Irene; Anderson, Edwin; Bajwa, Kanwaldeep; May, Ryan C.; Mizel, Steven B.; Graff, Aaron; Belshe, Robert B.
Abstract: Introduction: Intentional aerosolization of Yersinia pestis may result in pneumonic plague which is highly fatal if not treated early. Methods: We conducted a phase 1 randomized, double blind (within each group), placebo controlled, dose escalation trial to evaluate a plague vaccine, Flagellin/F1/V, in healthy adults aged 8 through 45 years. Vaccine was administered intramuscularly on Days 0 and 28 at a dose of 1, 3, 6 or 10 mcg. Subjects were observed for 4 h after vaccination for cytokine release syndrome. Reactogenicity and adverse events (AE) were collected for 14 and 28 days, respectively, after each vaccination. Serious AE were collected for the entire study. ELISA antibody and cytokines were measured at multiple time points. Subject's participation lasted 13 months. Results: Sixty healthy subjects were enrolled; 52% males, 100% non-Hispanic, 91.7% white and mean age 30.8 years. No severe reactogenicity events occurred; most AE were mild. No serious AE related to vaccine occurred. A dose response effect was observed to F1, V and flagellin. The peak ELISA IgG antibody titers (95% CI) after two 10 mcg doses of vaccine were 260.0 (102.6–659.0) and 983.6 (317.3–3048.8), respectively, against F1 and V antigens. The 6 mcg dose group provided similar titers. Titers were low for the placebo, 1 mcg and 3 mcg recipients. A positive antibody dose response was observed to F1, V and flagellin. Vaccine antigen specific serum IgE was not detected. There were no significant rises in serum or cellular cytokine responses and no significant IgG increase to flagellin after the second dose. Conclusion: The Flagellin/F1/V vaccine exhibited a dose dependent increase in immunogenicity and was well tolerated at all doses. Antibody specific responses to F1, V and flagellin increased as dose increased. Given the results from this trial, testing higher doses of the vaccine may be merited.